Transpuan di Masa Pandemi: Hak, Akses dan Eksklusi - Muh Wahyu; Abu Bakar; Muhammad Saleh Tajuddin (Badan Strategi Kebijakan Hukum, 2023)
Transwomen must contend with the fact that the state-mandated emergency status during a pandemic does not always make it easier for them to get essential services. This is especially noticeable during times of emergency when people's movement is restricted. The homo sacer idea proposed by Agamben is used in this article to define persons who are on the brink of protection for life. This circumstance is the result of a state of emergency, which is declared by the government as a justification for a crisis that has escalated into a pretext for violence and arbitrary action. The qualitative study methodology we employ explains how the state marginalized transwomen during the Covid-19 outbreak and how transwomen advocacy organizations are attempting to advance their causes. The study's overall finding is that transwomen are seen as homo sacer by the state, which has consequences for their ability to exercise their fundamental rights to healthcare and social support during the COVID-19 pandemic. We claim that the country's institutional apparatuses' unwillingness to incorporate transgender women in the Integrated Social Welfare Data (DTKS) demonstrates the existence of transgender exclusion symptoms. Transwomen must build networks with various non-governmental organizations and advocate for their own interests in order to fight for their rights. This is true for both transwomen without ID cards and those who do not receive social assistance.